BPA Alters Estrogen Receptor Expression in the Heart After Viral Infection Activating Cardiac Mast Cells and T Cells Leading to Perimyocarditis and Fibrosis - Bruno, Katelyn Ann; Mathews, Jessica Elizabeth; Yang, Alex Lingyun; Frisancho, J. Augusto; Scott, Ashley Jennie; Greyner, Henry David; Molina, Frank Anthony; Greenaway, Merci Shekinah; Cooper, George Maxwell; Bucek, Adriana; Morales-Lara, Andrea Carolina; Hill, Anneliese Ruth; et al. (Frontiers in Endocrinology, 2019)
Myocarditis is an inflammatory heart disease that leads to dilated cardiomyopathy (DCM) and heart failure. Sex hormones play an important role in the development of myocarditis with testosterone driving disease in males and estrogen being cardioprotective in females. The human population is widely exposed to the endocrine disruptor bisphenol A (BPA) from plastics such as water bottles, plastic food containers, copy paper and receipts. Several clinical and numerous animal studies have found an association between elevated BPA levels and cardiovascular disease. A recent report found elevated levels of BPA in the serum of patients with DCM compared to healthy controls. In this study we examined whether exposure to BPA for two weeks prior to viral infection and leading up to myocarditis at day 10 altered inflammation in female BALB/c mice housed in standard plastic cages/water bottles with soy-free food and bedding. We found that a human relevant dose of BPA (25µg/L) in drinking water, with an estimated exposure of 5µg BPA/kg BW, significantly increased myocarditis and pericarditis compared to control water without altering viral genome levels in the heart. BPA exposure activated ERa and ERb in the spleen 24 hours after infection and phosphorylated ERa and ERb during myocarditis, but decreased ERa and increased ERb mRNA in the heart as measured by qRT-PCR. Exposure to BPA significantly increased CD4+ T cells, IFNg, IL-17A, TLR4, caspase-1, and IL-1b in the heart. BPA exposure also increased cardiac fibrosis compared to controls. Mast cells, which are associated with cardiac remodeling, were found to increase in number and degranulation, particularly along the pericardium. Interestingly, plastic caging/water bottle exposure alone led to increased mast cell numbers, pericardial degranulation and fibrosis in female BALB/c mice compared to animals housed in glass cages/water bottles with soy-free food and bedding. These data suggest that BPA exposure may increase the risk of developing myocarditis after a viral infection in women.